Inhibition of LRRK2 kinase activity rescues deficits in striatal dopamine physiology in VPS35 p.D620N knock-in mice - Mengfei Bu; Jordan Follett; Isaac Deng; Igor Tatarnikov; Shannon Wall; Dylan Guenther; Melissa Maczis; Genevieve Wimsatt; Austen Milnerwood; Mark S. Moehle; Habibeh Khoshbouei; Matthew J. Farrer (npj Parkinson's Disease, 2023)
Abstract Dysregulation of dopamine neurotransmission profoundly affects motor, motivation and learning behaviors, and can be observed during the prodromal phase of Parkinson’s disease (PD). However, the mechanism underlying these pathophysiological changes remains to be elucidated. Mutations in vacuolar protein sorting 35 (VPS35) and leucine-rich repeat kinase 2 (LRRK2) both lead to autosomal dominant PD, and VPS35 and LRRK2 may physically interact to govern the trafficking of synaptic cargos within the endo-lysosomal network in a kinase-dependent manner. To better understand the functional role of VPS35 and LRRK2 on dopamine physiology, we examined Vps35 haploinsufficient (Haplo) and Vps35 p.D620N knock-in (VKI) mice and how their behavior, dopamine kinetics and biochemistry are influenced by LRRK2 kinase inhibitors. We found Vps35 p.D620N significantly elevates LRRK2-mediated phosphorylation of Rab10, Rab12 and Rab29. In contrast, Vps35 haploinsufficiency reduces phosphorylation of Rab12. While striatal dopamine transporter (DAT) expression and function is similarly impaired in both VKI and Haplo mice, that physiology is normalized in VKI by treatment with the LRRK2 kinase inhibitor, MLi-2. As a corollary, VKI animals show a significant increase in amphetamine induced hyperlocomotion, compared to Haplo mice, that is also abolished by MLi-2. Taken together, these data show Vps35 p.D620N confers a gain-of-function with respect to LRRK2 kinase activity, and that VPS35 and LRRK2 functionally interact to regulate DAT function and striatal dopamine transmission.